O022 Long-term cardiovascular risk in obstructive sleep apnoea: a sleep clinic cohort study. (7th October 2021) - Shenoy, B; Singh, B; Cadby, G; McQuillan, B; Hung, J; Rea, S; Walsh, J; Eastwood, P; Hillman, D; Mukherjee, S; Palmer, L; McArdle, N
Abstract: The relationship between obstructive sleep apnoea (OSA) and the development of long-term cardiovascular disease (CVD) is incompletely understood. We therefore investigated the impact of OSA severity, assessed by polysomnographic (PSG) metrics, on the development of long-term CVD in a sleep clinic cohort. Participants in the Western Australian Sleep Health Study, who attended a sleep clinic at a tertiary hospital between 2006 and 2010, were linked to state health administrative data from 1969 to 2016. Cox regression was used to investigate associations between standard PSG metrics of OSA severity (including the apnoea-hypopnoea index [AHI], time with oxygen saturation <90% [T90], and arousal index) and a CVD composite outcome (hospitalisation due to coronary heart disease, heart failure, stroke, or atrial fibrillation), controlling for baseline CVD risk factors such as age, sex, and body mass index (BMI). A total of 4067 participants were included: mean (SD) age of 50.6 (14.0) years, with 60.8% men. The mean BMI was 32.7 (7.7) kg/m². Over a median follow-up of 7.3 years, 584 (14.4%) participants developed the composite CVD outcome. Following adjustment for risk factors, independent predictors of incident CVD were an AHI ≥30 events/hour (hazard ratio [HR], 1.21; 95% CI, 1.02–1.45), log (T90 + 1) (HR, 1.16; 95% CI, 1.03–1.31), and the periodic limb movements of sleep index (PLMSI) (HR, 1.01; 95% CI, 1.00–1.01). We demonstrated independent effects of AHI, hypoxaemia, and PLMSI on incident CVD in this large sleep clinic cohort, suggesting multi-faceted aspects of disrupted sleep influence cardiovascular risk in OSA.